Three-dimensional evaluation of surgically assisted asymmetric rapid maxillary expansion - UĞURLU, FAYSAL; YILMAZ, HANİFE NURAY (MOSBY-ELSEVIER, 2019)
Introduction: Unilateral posterior crossbite is classified as true unilateral posterior crossbite (TUPC) or functional posterior crossbite (FPC). The differential diagnosis between TUPC and FPC is of utmost importance for the decision of expansion protocol because conventional expansion methods have some shortcomings for TUPC. The aim of this retrospective study was to 3-dimensionally evaluate the effects of asymmetric rapid maxillary expansion combined with unilateral osteotomy. Methods: This study sample comprised 16 patients (mean age 18.38 +/- 6 1.45) with TUPC. A Hyrax acrylic cap included the maxillary premolars and molars on the constricted side, and all teeth up to the central incisor were included on the other side to increase anchorage. Unilateral surgically assisted rapid maxillary expansion was performed and included anterior (aperture piriformis), lateral (zygomatic buttress), and posterior (pterygomaxillary junction) osteotomies on the constricted side and separation of the midpalatal suture. Cone-beam computed tomographic scans taken just before the operation and after 6 months of retention were used to assess skeletal, dental, and periodontal changes. Results: Expansion was seen on both sides; however, the amount of expansion and tipping was higher on the osteotomy+ side. Because the canines were not included in the acrylic cap on the osteotomy+ side, they did not present the same amount of tipping as the ipsilateral posterior teeth. More teeth were affected periodontally on the osteotomy- side; however, there were no clinically significant differences between the osteotomy+ and osteotomy+ sides (mean differences range +10.54 to -0.57 mm). The aperture piriformis width increased significantly on the osteotomy+ side. Conclusions: The treatment mechanics had no clinically detrimental effects on the supporting alveolar bone of the maxilla on either side, and it was thought to be effective in cases with TUPC; however, case selection is crucial.
Keywords: BEAM COMPUTED-TOMOGRAPHY; SKELETAL; CHILDREN; MALOCCLUSION; OCCLUSION; APPLIANCE